Search for clinical, genetic, morphological and immunohistochemical predictors of parathyroid cancer recurrence - Ekaterina I. Kim; Anna K. Eremkina; Alina R. Elfimova; Natalia G. Mokrysheva (Терапевтический архив)
Background. Currently, there is no consensus on postoperative risk stratification for parathyroid cancer (PC). The risk factors of disease progression are crucial for choosing the optimal treatment strategy, including adjuvant methods and patient,s follow-up.